The Impacts of COVID-19 on the Well-Being of students with SEN in Primary Stage in Dubai Schools - ABUSNENEH, NOOR (2022)
The current paper aimed to verify the impact of the Covid-19 pandemic on the well-being of a sample of (74) students who were classified by teachers as a student with Special Educational Needs in five of Dubai primary schools. The study methodology depended on the descriptive-analytical approach, the researcher prepared a well-being questionnaire for students with special educational needs SEN, and its validity and reliability were verified. Findings indicated a decrease in the levels of well-being among the study sample as a result of their Well-being affected by the pandemic, while there were no statistically significant differences between the various disabilities ( learning difficulties - hyperactivity - hearing impairment - visual impairment - mild speech disorder) in their average levels of well-being, while it became clear that there are some differences between males and females in the average Well-being scores in favour of males, and their average Well-being scores were high compared to females. As for the place of residence and the school stage, there were no statistically significant differences between the average scores of the sample members in the two variables, and the study recommended the need to provide counselling programs to improve the well-being of the students with SEN due to the circumstances imposed on them by the COVID-19 pandemic.